Efeito da utilização de três diferentes rações comerciais na produção de tambaqui (Colossoma macropomum): qualidade de água e desempenho zootécnico - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2018)
In trade there is a range of rations available with different approaches, concepts, nutritional profiles and commercial value in order to meet the varied demands and market niches. This wide diversity of options often confuses producers at the time of their choice of feed, which take into account the financial issue rather than the quality of the feed. In this way, the choice of ration to be used in the production of a certain species is fundamental to seek the maximization of production and profitability in fish farming. Therefore, the objective of this work was to compare the utilization of three commercialized rations in the region of Santarém-PA, in order to contribute to the efficiency of the production of tambaqui (Colossoma macropomum) and to improve the income of the region's producers. The experiment lasted 30 days, comparing three commercial diets with different formulations and commercialization prices used in the production of fish, called rations A, B and C, with three replicates each. Tambaquis with a mean weight of 24.75 g ± 6.69 g were stored at a density of 25 fish/box (83 fish/m3) in nine tanks with a volume of 500 liters (useful volume of 300 liters). The fish were fed twice a day (9:00 a.m. and 5:00 p.m.) and the feeding rate was 3% of the total biomass throughout the experimental period, the amount of feed being adjusted according to the results obtained in the biometrics that were performed within 10 days. The physical and chemical variables such as water temperature (° C), dissolved oxygen (mg/L), electrical conductivity (μSm / cm) and pH were recorded daily (8:30 and 2:00 p.m.). A daily exchange of 80% of the water volume of each experimental unit was carried out. Tests of buoyancy and measurements on the grain size of the different rations were carried out. Among the rations used in this experiment, we can verify that all of them had similar results in water quality parameters and remained within the ranges considered ideal for the production of tropical fish. Regarding the zootechnical and economic parameters, it was observed that the zootechnical parameters were very similar with the different rations used, however, the treatment B obtained lower value per kg of fish produced (R$ 2.82) and presented as the with a better cost/benefit ratio for the producer in the region of Santarém-PA.
Keywords: Qualidade de água; Ração; Produtividade; Recursos Pesqueiros/Zootecnia